Varnost pomorskega prometa v obdobju digitalizacije in regionalnih konfliktov - Grbec, Mitja (Podjetje in delo, 2024)
The paper discusses maritime safety in the Adriatic Sea and Ionian Sea in the context of digitalisation and regional conflicts. It lists existing international agreements and proposes upgrades considering new technological solutions and lessons learned from current regional conflicts. The paper emphasises the importance of a two-tier approach in establishing a ship reporting and routing system (bilateral and trilateral agreements between the Adriatic states, and confirmation by IMO) and the role of the European Union in ensuring maritime safety. Particular attention is given to the impact of the Red Sea crisis on global supply chains and the right to transit passage in the region, highlighting significant legal and operational challenges and the role of digitalisation in enhancing security. The impact of the crisis on maritime traffic in the Adriatic Sea, particularly on cargo handling in the northern Adriatic ports, with a special emphasis on the port of Koper (Luka Koper d.d.), is also discussed. It concludes with an assessments of necessary upgrades and suggestions for improving existing agreements.
Keywords: Digitalizacija; Pomorski prevoz